If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -9) + 61 = -5(x + -9) + 16x + -29 Reorder the terms: 4(-9 + 2x) + 61 = -5(x + -9) + 16x + -29 (-9 * 4 + 2x * 4) + 61 = -5(x + -9) + 16x + -29 (-36 + 8x) + 61 = -5(x + -9) + 16x + -29 Reorder the terms: -36 + 61 + 8x = -5(x + -9) + 16x + -29 Combine like terms: -36 + 61 = 25 25 + 8x = -5(x + -9) + 16x + -29 Reorder the terms: 25 + 8x = -5(-9 + x) + 16x + -29 25 + 8x = (-9 * -5 + x * -5) + 16x + -29 25 + 8x = (45 + -5x) + 16x + -29 Reorder the terms: 25 + 8x = 45 + -29 + -5x + 16x Combine like terms: 45 + -29 = 16 25 + 8x = 16 + -5x + 16x Combine like terms: -5x + 16x = 11x 25 + 8x = 16 + 11x Solving 25 + 8x = 16 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 25 + 8x + -11x = 16 + 11x + -11x Combine like terms: 8x + -11x = -3x 25 + -3x = 16 + 11x + -11x Combine like terms: 11x + -11x = 0 25 + -3x = 16 + 0 25 + -3x = 16 Add '-25' to each side of the equation. 25 + -25 + -3x = 16 + -25 Combine like terms: 25 + -25 = 0 0 + -3x = 16 + -25 -3x = 16 + -25 Combine like terms: 16 + -25 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 24+3(-6)=8x-74 | | 4x+3x^2=6 | | 6u-14=14u | | 6(6b+7)= | | 84=-3(6r+8) | | 35=6y-1 | | 5x+10=90+x | | 46=7z+4 | | 0.8d+0.4=-5.2 | | 3(y+6)-8(5y-6)=-37y+4 | | 10x-23+6x+11=180 | | 2x+6=9x^2 | | 7(y+3)=-2(2y-3)+5y | | 7x+6y=54 | | 4k-8=12+2k | | 4(4x+4)-12= | | 2x^2+15x=6x+35 | | -4(3+7r)=-124 | | -2(1-5x)=-12+5x | | 3-4y=2x | | 15f-2=43 | | d+3d+(3d+10)=135 | | 9b-5=-77 | | -8(n-4)=88 | | 2x^4+3x^2-9=0 | | 2(x+5)-4x=24 | | F(x)=x^2-10x-16 | | 5(x-2)+4x=-82 | | -6+2n=n-6(1-6n) | | 5y-7x+15=0 | | 4(u-5)-6=-4(-6u+4)-8u | | x^3+3x^2-37x-15=0 |